Características fenotípicas e filogenéticas de isolamentos de Sporothrix spp. isolados de casos clínicos atendidos no Hospital das Clínicas da UFMG em Belo Horizonte - Augusto César Parreiras de Jesus (2020)
Sporotrichosis is a subcutaneous mycosis, rarely systemic, caused by a complex of dimorphic fungi in the genus Sporothrix spp. In Brazil reports of human epidemics of sporotrichosis involving feline zoonotic transmission is common. The most frequent isolated species is S. brasiliensis, although S. schenckii sensu sctricto has been also recorded. Laboratory characterization of the etiological agent in culture is usually done at the genus level, according to its phenotypic characteristics at 25°C and 37°C. The objectives of this research were the characterization of the phenotypic and phylogenetical features of clinical isolates of patients with sporotrichosis, confirmed by culture on Sabouraud Dextrose Agar (SDA) and its correlation with the patient’s clinical data. The cultures were collected in the microbiology section of the Clinical Pathology Unit at the “Hospital das Clínicas (HC) of “Universidade Federal de Minas Gerais (UFMG)”, from patients diagnosed with active sporotrichosis. Patient data were reviewed from their respective medical records available at the HC. Between 2017 and 2018, 49 isolates of Sporothrix spp. were collected of which only 30 were viable at the time of the analysis. The 30 isolates in this study were collected from 26 patients. The isolates were cultured in ASD broth, and their DNA extraction was performed according to traditional molecular techniques. The amplification of the Internal Transcribed Spacers gene (ITS1, 5.8S and ITS2) using the universal primers ITS1 and ITS 4, was by PCR (polymerase chain reaction) and their amplicons sequenced and then deposited at the National Center for Biotechnology Information (NCBI). Phylogenetic analyzes was performed using Maximum Likelihood in MEGA X software. The data collected show that the common clinical manifestation of the disease was the lymphocutaneous form (76.9%). The upper limbs (57.7%) were frequently affected. Most of the infected patients reported contact with cats infected with Sporothrix spp. (69.3%). 76.9% of patients were adults at the time of infection. Gender preference was not observed. Our phylogenetic analyzes revealed that there were several Sporothrix species circulating in Minas Gerais. The data showed S. brasiliensis as the most frequent species, followed by S. schenckii and S. globosa. There was not direct relationship between the clinical form in the investigated patients and the infecting species. In this study most human cases were in contact with infected cats; thus, their cases were considered putatively related to zoonotic transmission.